Tumour-infiltrating lymphocytes predict response to definitive chemoradiotherapy in head and neck cancer - Balermpas, P (Nature Publishing Group, 2014)
BACKGROUND: We aimed to investigate the prognostic value of tumour-infiltrating lymphocytes' (TILs) expression in pretreatment specimens from patients with head and neck squamous cell carcinoma (HNSCC) treated with definitive chemoradiotherapy (CRT). METHODS: The prevalence of CD3+, CD8+, CD4+ and FOXP3+ TILs was assessed using immunohistochemistry in tumour tissue obtained from 101 patients before CRT and was correlated with clinicopathological characteristics as well as local failure-free- (LFFS), distant metastases free- (DMFS), progression-free (PFS) and overall survival (OS). Survival curves were measured using the Kaplan–Meier method, and differences in survival between the groups were estimated using the log-rank test. Prognostic effects of TIL subset density were determined using the Cox regression analysis. RESULTS: With a mean follow-up of 25 months (range, 2.3–63 months), OS at 2 years was 57.4% for the entire cohort. Patients with high immunohistochemical CD3 and CD8 expression had significantly increased OS (P=0.024 and P=0.028), PFS (P=0.044 and P=0.047) and DMFS (P=0.021 and P=0.026) but not LFFS (P=0.90 and P=0.104) in multivariate analysis that included predictive clinicopathologic factors, such as age, sex, T-stage, N-stage, tumour grading and localisation. Neither CD4 nor FOXP3 expression showed significance for the clinical outcome. The lower N-stage was associated with improved OS in the multivariate analysis (P=0.049). CONCLUSION: The positive correlation between a high number of infiltrating CD3+ and CD8+ cells and clinical outcome indicates that TILs may have a beneficial role in HNSCC patients and may serve as a biomarker to identify patients likely to benefit from definitive CRT.